No evidence for the use of magnetic declination for migratory navigation in two songbird species. - Nikita Chernetsov (PLoS ONE, 2020)
Determining the East-West position was a classical problem in human sea navigation until accurate clocks were manufactured and sailors were able to measure the difference between local time and a fixed reference to determine longitude. Experienced night-migratory songbirds can correct for East-West physical and virtual magnetic displacements to unknown locations. Migratory birds do not appear to possess a time-different clock sense; therefore, they must solve the longitude problem in a different way. We showed earlier that experienced adult (but not juvenile) Eurasian reed warblers (Acrocephalus scirpaceus) can use magnetic declination (the difference in direction between geographic and magnetic North) to solve this problem when they were virtually displaced from Rybachy on the eastern Baltic coast to Scotland. In this study, we aimed to test how general this effect was. Adult and juvenile European robins (Erithacus rubecula) and adult garden warblers (Sylvia borin) under the same experimental conditions did not respond to this virtual magnetic displacement, suggesting significant variation in how navigational maps are organised in different songbird migrants.